Become Recognized Minority in a Multicultural Society: An- Naim’s Theory in Responding to Ahmadiyyah Cases in Indonesia - Muta Ali Arauf (Indonesian Academy of Social and Religious Research (IASRR), 2022)
This study aims to analyze the thoughts of Abdullah Ahmed an-Naim related of constitutionalism, human rights and citizenship based on justice in minority groups. An-Naim’s thoughts on human rights can be accommodated to public expectations regarding the issue of the Ahmadiyya community in Indonesia. Read an-Naim’s theory regarding women, non-Muslim status and apostasy. The issue of human rights initiated by an-Naim will be the basic foundation in the explicit explanation of this paper. Considering the existing social values based on the enforcement of human rights in Indonesia, the position of the Ahmadiyya community must be positioned equally in the law in terms of rights and obligations as part of Indonesian citizens. The state must be neutral considering the Ahmadiyya community in responding to its religious existence. The government must maintain neutrality in regulating religious life for every citizen in order to create an atmosphere of harmony and peace. This paper attempts to produce a peaceful religious discourse in the context of religious freedom in Indonesia